2020
DOI: 10.1016/j.pld.2020.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Extreme plastid RNA editing may confound phylogenetic reconstruction: A case study of Selaginella (lycophytes)

Abstract: Cytidine-to-uridine (C-to-U) RNA editing is common in coding regions of organellar genomes throughout land plants. In most cases RNA editing alters translated amino acids or creates new start codons, potentially confounds phylogenetic reconstructions. In this study, we used the spike moss genus Selaginella (lycophytes), which has the highest frequency of RNA editing, as a model to test the effects of extreme RNA editing on phylogenetic reconstruction. We predicted the C-to-U RNA editing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 42 publications
4
25
0
Order By: Relevance
“…As suggested in Figure 4, different taxonomic groups have different RNA editing types and numbers. Selaginellaceae plastomes show high levels of C-to-U RNA editing, consistent with the high occurrence of C-to-U RNA editing reported in Selaginella plastomes [71,72]. By contrast, we found that Lycopodiaceae mainly shows U-to-C RNA editing, and two completely different clades are present in Isoëtaceae plastomes: one shows almost all C-to-U editing, and the other shows two types coexist.…”
Section: Plastomic Diversity Of Lycophytessupporting
confidence: 89%
See 1 more Smart Citation
“…As suggested in Figure 4, different taxonomic groups have different RNA editing types and numbers. Selaginellaceae plastomes show high levels of C-to-U RNA editing, consistent with the high occurrence of C-to-U RNA editing reported in Selaginella plastomes [71,72]. By contrast, we found that Lycopodiaceae mainly shows U-to-C RNA editing, and two completely different clades are present in Isoëtaceae plastomes: one shows almost all C-to-U editing, and the other shows two types coexist.…”
Section: Plastomic Diversity Of Lycophytessupporting
confidence: 89%
“…Therefore, Isoëtaceae plastomes with slower base substitution rates are more likely to retain more RNA-editing sites than Lycopodiaceae plastomes ( Figure 3 and Figure 4 ). However, given the particularity of the high occurrence of RNA editing in both Selaginella plastid and mitochondrial genomes [ 66 , 71 , 72 ], this model cannot account for the RNA editing of Selaginellaceae. Instead, some site recognition factors for editing events in the Selaginella genome may be associated with the abundance of organelle RNA editing [ 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…This conflict arising from the mitochondrial data cannot be explained by the presence of extensive RNA editing sites in the mitochondrial data (Fig. 1c ), which in some cases has been reported to bias phylogenetic inferences 25 , 26 , and instead may be best explained by incomplete lineage sorting, which is supported by our PhyloNet 27 and coalescent analyses of nuclear genes (Supplementary Note 5 ).…”
Section: Phylogeny Of Cycads and Seed Plantsmentioning
confidence: 54%
“…Spring (Oldenkott & al., 2014). Du & al. (2020) proposed that the extreme RNA editing frequency might confound phylogenetic reconstruction and recommended to restore RNA editing sites when using organellar genes with abundant RNA editing sites in phylogenetic studies.…”
Section: ■ Discussionmentioning
confidence: 99%
“…RNA editing sites prediction. -Massive cytidine-touridine (C-to-U) RNA editing sites have been reported in the Selaginella chloroplast genomes (Oldenkott & al., 2014;Smith, 2020;Shim & al., 2021), which might confound phylogenetic reconstruction (Du & al., 2020). We extracted proteincoding sequences (CDS) of the chloroplast genomes using Geneious v.11.1.4 (Kearse & al., 2012) and then predicted the C-to-U RNA editing sites using the online tool PREPACT 3 (Lenz & al., 2018) under BLASTX mode with S. uncinata plastid protein database as reference.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%